2016
DOI: 10.1002/2016jg003450
|View full text |Cite
|
Sign up to set email alerts
|

Winter soil respiration in a humid temperate forest: The roles of moisture, temperature, and snowpack

Abstract: Winter soil respiration at midlatitudes can comprise a substantial portion of annual ecosystem carbon loss. However, winter soil carbon dynamics in these areas, which are often characterized by shallow snow cover, are poorly understood due to infrequent sampling at the soil surface. Our objectives were to continuously measure winter CO2 flux from soils and the overlying snowpack while also monitoring drivers of winter soil respiration in a humid temperate forest. We show that the relative roles of soil tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…Forest canopies composed of mixed tree species are apparently more vulnerable to snow damage than forest canopies composed of one tree species (Diaz-Yanez et al 2017). In addition, the snowpack in winter can also change soil carbon emission by affecting soil temperature and moisture (Contosta et al 2016). Consistent with the latter result, a meta-analysis revealed that an increase in snowpack depth can increase soil respiration and microbial biomass by increasing soil temperature and water content (Li et al 2016).…”
Section: Introductionsupporting
confidence: 58%
“…Forest canopies composed of mixed tree species are apparently more vulnerable to snow damage than forest canopies composed of one tree species (Diaz-Yanez et al 2017). In addition, the snowpack in winter can also change soil carbon emission by affecting soil temperature and moisture (Contosta et al 2016). Consistent with the latter result, a meta-analysis revealed that an increase in snowpack depth can increase soil respiration and microbial biomass by increasing soil temperature and water content (Li et al 2016).…”
Section: Introductionsupporting
confidence: 58%
“…Previous studies indicated that there is still a lot of nongrowing season Rs under snowpack and can globally contribute 5% to 60% of the total annual carbon dioxide flux from soils during nongrowing season [15,16]. However, in many temperate ecosystems, climate changes have been and will continue to be more pronounced during the nongrowing season than during the growing season [17].…”
Section: Introductionmentioning
confidence: 99%
“…Using the CO 2 concentrations at each depth, we calculated CO 2 production within each depth using the following series of equations based on Fick's Law (Tang et al 2003;Moyes and Bowling 2013;Contosta et al 2016;Hicks Pries et al 2017) (Eq. 1).…”
Section: Soil Co 2 Productionmentioning
confidence: 99%